Chaotic dynamics in a flexible exchange rate system:A study of noise effects - Toichiro Asada; Tetsuya Misawa; Toshio Inaba (Discrete Dynamics in Nature and Society)
In this paper, we investigate by means of analytical method and numerical simulations the properties of three-dimensional business cycle model, in which foreign exchange rate is flexible and a parameter is fluctuated by noise. The model is a discrete time version of Asada (Journal of Economics, 62, 239–269,1995)'s continuous time open economy model without noise. We show (1) noise may suppress the burst of flexible foreign exchange rate when its behavior begins to burst as a bifurcation parameter (adjustment speed of the goods market) is increased, (2) the windows of cycles can be broken by noise, and (3) noise may reveal the hidden structures.